SELEKSI POHON BENIH Gmelina arborea Roxb. PADA HUTAN RAKYAT DI BONDOWOSO, JAWA TIMUR Selection of Seed Trees of Gmelina arborea Roxb. at Smallholder Forest In Bondowoso, East Java - Hamdan Adma Adinugraha; Dedi Setiadi (Jurnal Hutan Tropis, 2018)
Gmelina arborea is one plant spacies that is widely planted in smallholder forests in Bondowoso, East Java. This research was conducted in the framework of the selection of seed sources that can be developed for proiduksi quality seeds. The results showed that a relatively equitable distribution of forest people in four districts with three patterns that monoculture, mixtures and intercropping with agricultural crops. Parent tree bole height average of 10.60 m with a trunk diameter/ 25.39 cm dbh. there are 2 types of fruit is round and slightly oval with the number of seeds per kilogram of grain in 1872 and 1000 grain weight of seed on average 538.75 grams indicates the variation differed significantly between the parent tree.Key Words: Gmelina arborea; seed trees; selection; smallholder forest